SUGAR BOARDS IN CBSE SCHOOLS: A STRATEGIC SCHOOL-BASEDAPPROACH TO REDUCE SUGAR CONSUMPTION AMONG INDIAN STUDENTS - APARNA KUNA, KESHAVI KILLI, DILIP KUMAR KANDAR; SUPTA SARKAR (The Journal of Research, PJTSAU, 2026)
Unhealthy sugar consumption in childhood remains a serious public health concern, contributing to rising rates of obesity, diabetes and dental disease. School-based initiatives that raise awareness and promote healthier eating habits offer a practical and adaptable pathway to address this issue. This paper synthesizes current scientific evidence on the health impacts of excessive sugar intake among children, assesses intake patterns among Indian school-aged populations, and reviews global and national interventions effective in reducing childhood sugar consumption. Unlike a conventional narrative review, this article integrates scientific evidence, policy guidance, and international best practices to develop a practical implementation framework tailored to CBSE schools. Drawing on international best practices and adapting them to the Indian educational ecosystem, the framework integrates five core pillars: curriculum-linked visual boards, interactive student activities, parent and community engagement, multi-stakeholder collaboration, and advocacy for supportive policies. A concise monitoring and evaluation approach is outlined to assess implementation fidelity, student behavior change and school-level policy compliance. This paper translates policy into action by proposing a practical and scalable school-based intervention that supports India’s broader goals for noncommunicable disease prevention.